Asedio a Dilthey : un ensayo de interpretación - Imaz, Eugenio, 1900-1951 (Book collections on Project MUSE., 1945)
This work interprets Dilteyan thought, the first paragraphs that refer to the composition of the volume, are in small print, a letter that the reader can save or return to it if he deems it appropriate so as not to lose the thread. Because the thread runs from prologue to prologue, and not precisely the one that sews the sheets for this day. It is an approach to the work of Dilthey, in which problems have been planted, tried to solve later by returning to questions already started, repeating expositions, all this in a deliberate mimicry in the Diltheyan way, a non-naturalistic mimicry, of grasshoppers or butterfly, but hermeneutic: pampering on the inside, and not only with the head, which on the inside moved him not to let his hand rest throughout his life. The reader will judge whether the procedure is recommended, since not on all occasions, in this exceptional way to express clearly and briefly the broad and impetuous current of one of the most considerable thinkers of the time.